Formulasi dan Evaluasi Larutan Pencuci Mulut dengan Bahan Antimikroba Senyawa 1,5-Bis (3’-Etoksi-4’-Hidroksifenil)-1,4-Pentadien-3-on - Esti Mumpuni; Agus Purwanggana; Esti Mulatsari; Ryan Pratama (Fakultas Farmasi Universitas Pancasila, 2019)
1,5-bis (3-ethoxy-4-hydroxyphenyl) -1,4-pentadien-3-one (EHP) compound is an analogous compound of curcumin which has antimicrobial activity. In this study, the formulation and evaluation of mouthwash was carried out with EHP as an antimicrobial ingredient. The formulation of mouthwash was made with various concentrations of EHP 3, 6, 12, 16 and 18 ppm. Evaluation of mouthwash included organoleptic test, pH, clarity, density and antimicrobial activity against Staphylococcus aureus, Steptococcus mutans, and Candida albicans. Antimicrobial test was done by agar diffusion method. The results of organoleptic test obtained mouthwash was clear blue liquid, the aroma of mint, and fresh cold taste; pH range of 6.15 - 6.74; density of 1.0419 - 1.0561 g/cm3. The evaluation of mouthwash showed that the mouthwash was stable in storage for 1 month at 40 °C. Antimicrobial tests showed the diameter of inhibitory zone against Staphylococcus aureus (ATCC 6538); Streptococcus mutans (ATCC 31987) and Candida albicans (ATCC 10231) ranged from 6.2 to 8.4 mm at the concentration of EHP 18 bpj. The results showed that EHP compound was potential as antimicrobial ingredient in moutwash formula.